THE REALIZATION OF IMPOLITENESS STRATEGIES USED BY STUDENTS IN ENGLISH ONLINE LEARNING THROUGH ZOOM DURING PANDEMIC COVID-19 - Suchroni . Panjaitan; Sumarsih . Sumarsih; Siti Aisyah Ginting (Universitas Negeri Medan, 2022)
Corona Virus Disease 2019 (COVID-19) was detected in China in December 2019, spread throughout the world within a few months and was declared a pandemic by the World Health Organization (WHO) on 11th March 2020. It also has hit Indonesia since March 2020. It affects 90.2% of students worldwide, in which 1.57 billion students are absent from school and 191 countries including Indonesia. Unfortunately, the observation found that the students often say impolite language, such as mock their friends, change their friends’ name, and have high intonation when they were uttering their opinion during online teaching and learning process through Zoom. It is very serious problem because impoliteness happened during the main activity. The objective of the study was to find out the realizations of impoliteness strategies used by students in English online learning through Zoom during pandemic Covid-19. The study was descriptive qualitative. The subject of the study was VII grade of SMP Ar-Rahman Percut. The data of the study was impoliteness clauses which are recorded from the students’ interaction. The finding of the study, there were eight realizations of impoliteness strategies found in this study, they are be disinterested, unconcerned, unsympathetic; use inappropriate identity marker; use obscure or secretive language; seek disagreement; use taboo words; call the other name; frighten; and condescend, scorn or ridicule. Then, there were three additional realizations, they are employing insincere; direct speech, clear, unambiguous; and invade the other’s space. Keywords: Impoliteness, Students in English Online Learning, Zoom, Covid-19